DIGITAL CAPABILITY AND MARKETING EFFECTIVENESS IN REGIONAL SUPERMARKETS: MODERATING EFFECTS OF MARKET MATURITY - Jiang Jialing (Scientific Research and Experimental Development, 2026)
This study examines the direct impact of digital capability on marketing effectiveness among regional supermarkets, and explores the moderating role of market maturity in this relationship. Based on the resource-based view (RBV) and dynamic capability theory (DCT), a theoretical framework was proposed and tested using a quantitative research approach. Data were collected via a structured questionnaire from 312 senior managers and marketing directors of regional supermarkets across 12 provinces in China. Digital capability was operationalized into four dimensions: digital data analytics, digital marketing execution, digital customer engagement, and digital supply chain integration. Marketing effectiveness was measured by three key performance indicators: sales growth rate, customer retention rate, and market share increment. Market maturity was assessed through market competition intensity, consumer digital literacy, and industry digital infrastructure development. The results of hierarchical regression analysis indicated that digital capability exerts a significant positive effect on marketing effectiveness (β = 0.523, p < 0.001). Furthermore, market maturity positively moderates the relationship between digital capability and marketing effectiveness (β = 0.196, p < 0.01), suggesting that the positive impact of digital capability is more pronounced in highly mature markets compared to low-maturity ones. This study contributes to the existing literature by providing a nuanced understanding of how digital capability drives marketing outcomes in the regional retail context, and by identifying market maturity as a critical boundary condition. Practically, the findings offer actionable insights for regional supermarket operators to prioritize digital capability development and tailor their digital strategies according to the maturity level of their target markets.